Myths and misunderstandings in white-collar crime / Miriam H. Baer, Brooklyn Law School. - Baer, Miriam H. (Cambridge University Press, 2023)
Myths and Misunderstandings in White Collar Crime uses real world examples to explore the pathologies that hamper our ability to understand and redress white-collar crime. The book argues that several misinterpretations about white-collar crime continue to impede its enforcement, including: its failure to be classified according to degrees of severity in many jurisdictions; its failure to statutorily parse groups of defendants into major and minor players; and the failure of statutes to effectively define crimes, leading to the prosecution of 'unwritten' crimes. Miriam Baer offers a step-by-step framework, informed by theories of institutional design and behavioral psychology, for redressing these misunderstandings through 'code design,' or paying greater attention to how we write, frame, and lay out our federal criminal code, as a roadmap to more coherent and useful laws. A clearer, subdivided criminal code paves the way for a discussion of white-collar crime unmarred by myths and misunderstandings.